Dilema Pembangunan di Indonesia: Analisis Mengenai Dampak dan Implikasi Kebijakan Pembangunan Era Presiden Joko Widodo - Rafi Aufa Mawardi (Jurnal Mengkaji Indonesia, 2023)
Abstract: Under the leadership of President Joko Widodo, Indonesia carried out a massive escalation and acceleration of development. The development configuration that focuses on infrastructure is directly proportional to economic growth at 5.31%. However, this has resulted in various fundamental problems and implications for dependence on foreign countries. This study analyzes development policies in Indonesia and their impacts and implications for various sectors. This study uses qualitative research methods with a literature study approach and the paradigm of modernization and dependency as an analytical framework. This research reveals that infrastructure-oriented development in Indonesia has left several problems in social, culture, economic and environmental aspects. Besides that, the linear implication of development in Indonesia is the occurrence of dependence between Indonesia and foreign countries along with the high amount of debt and investment. Purpose: This study aims to analyze in depth about development in Indonesia using two paradigms, namely the modernization paradigm and the dependency paradigm. Design/Methodology/Approach: This study used a qualitative research method with a literature study approach. Findings: This research found that the reality of infrastructure-oriented development in Indonesia gave birth to various problems in social, culture, economic and environmental aspects. In addition, this development coherently has implications for dependence between Indonesia and foreign countries in line with the high amount of debt and investment. Originality/Value: This research explains comprehensively the impacts and implications of infrastructure development in Indonesia in terms of social, economic and environmental dimensions. Then, this study conducts an in-depth analysis using two development paradigms, namely modernization and dependency.